Effects of mycogenic silver nanoparticles on organisms of different trophic levels - Assis da Silva, Carolina [UNESP]; Ribeiro, Bruna Marques [UNESP]; Trotta, Caterina do Valle [UNESP]; Perina, Fernando Cesar [UNESP]; Martins, Roberto; Moledo de Souza Abessa, Denis [UNESP]; Barbieri, Edison; Simões, Marta Filipa; Ottoni, Cristiane Angélica [UNESP] (My University, 2022)
Biogenic silver nanoparticles (AgNPs) are considered a promising alternative to their synthetic versions. However, the environmental impact of such nanomaterials is still scarcely understood. Thus, the present study aims at assessing the antimicrobial action and ecotoxicity of AgNPs biosynthesized by the fungus Aspergillus niger IBCLP20 towards three freshwater organisms: Chlorella vulgaris, Daphnia similis, and Danio rerio (zebrafish). AgNPs IBCLP20 showed antibacterial action against Klebsiella pneumoniae between 5 and 100 μg mL−1, and antifungal action against Trichophyton mentagrophytes in concentrations ranging from 20 to 100 μg mL−1. The cell density of the microalgae Chlorella vulgaris decreased 40% after 96 h of exposure to AgNPs IBCLP20, at the highest concentration analysed (100 μg L−1). The 48 h median lethal concentration for Daphnia similis was estimated as 4.06 μg L−1 (2.29–6.42 μg L−1). AgNPs IBCLP20 and silver nitrate (AgNO3) caused no acute toxicity on adult zebrafish, although they did induce several physiological changes. Mycosynthetized AgNPs caused a significant increase (p < 0.05) in oxygen consumption at the highest concentration studied (75 μg L−1) and an increase in the excretion of ammonia at the lower concentrations, followed by a reduction at the higher concentrations. Such findings are comparable with AgNO3, which increased the oxygen consumption on low exposure concentrations, followed by a decrease at the high tested concentrations, while impairing the excretion of ammonia in all tested concentrations. The present results show that AgNPs IBCLP20 have biocidal properties. Mycogenic AgNPs induce adverse effects on organisms of different trophic levels and understanding their impact is detrimental to developing countermeasures aimed at preventing any negative environmental effects of such novel materials.
Keywords: Aspergillus niger; Chlorella vulgaris; Danio rerio.; Daphnia similis; Klebsiella pneumoniae; Mycogenic silver nanoparticles